2010
DOI: 10.1007/s00467-010-1536-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical correlates of microalbuminuria in children with sickle cell disease

Abstract: Sickle cell disease (SCD) is associated with a large spectrum of renal abnormalities, one of which, microalbuminuria/proteinuria (MA/P), is a known predictor of end-stage renal disease. We studied 90 children with SCD (57% male; mean age 11.4 +/- 5.2 years) to determine the prevalence and examine clinical correlates of MA/P. The average of two spot urine microalbumin-to-creatinine samples obtained 6 months apart was recorded. Medical records were reviewed for demographic and biochemical data. Medication use, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 24 publications
7
64
1
Order By: Relevance
“…In children with SCA, significant associations have been found between proteinuria and the hemolysis markers of low hemoglobin (Hb) and high lactate dehydrogenase (LDH). 5,13 Similar studies in adults, however, have not replicated this finding, although an association between low hemoglobin levels and hyperfiltration have been reported. [14][15] More recently, Maier-Redelsperger et al utilized a marker of red cell survival derived from mature red blood cell hemoglobin (RBC Hb) and reticulocyte hemoglobin (RET Hb), and showed that the log (RBC Hb/RET Hb) was highly correlated with LDH, bilirubin and albuminuria.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In children with SCA, significant associations have been found between proteinuria and the hemolysis markers of low hemoglobin (Hb) and high lactate dehydrogenase (LDH). 5,13 Similar studies in adults, however, have not replicated this finding, although an association between low hemoglobin levels and hyperfiltration have been reported. [14][15] More recently, Maier-Redelsperger et al utilized a marker of red cell survival derived from mature red blood cell hemoglobin (RBC Hb) and reticulocyte hemoglobin (RET Hb), and showed that the log (RBC Hb/RET Hb) was highly correlated with LDH, bilirubin and albuminuria.…”
Section: Introductionmentioning
confidence: 90%
“…4 It is thought that chronic ischemia secondary to repeated vasoocclusive events in the microvasculature of the renal medulla results in a prostaglandin-induced increase in total renal plasma flow leading to the raised glomerular filtration rate (GFR) seen in childhood and early adulthood. [4][5] Prolonged hyperfiltration eventually leads to glomerular sclerosis and the GFR decreases towards normal as the patient ages. 4 In some, this decline is accelerated and continuous resulting in end-stage renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…Macroalbuminuria is a sensitive primary indicator of glomerulopathy, preceding the development of progressive renal insufficiency (Guasch et al, 1999) and ultimately leading to end-stage renal disease (ESRD) in both children and adults (Becton et al, 2010;Guasch et al, 1999Guasch et al, , 2006. Focal segmental glomerulosclerosis (FSGS) and collapsing glomerulosclerosis are subtypes of podocytopathies and podocyte injury, which is proposed to play a key role in the development and progression of kidney disease (Barisoni and Nelson, 2007).…”
Section: Sickle Cell and Cardiovascular Disease Genetics 583mentioning
confidence: 99%
“…Microalbuminuria has also been investigated in numerous nephrologic and other diseases, such as microhaematuria [56], sickle cell anemia [30,57], low-birth weight [58], congenital solitary kidneys [59], orthostatic proteinuria [34], metabolic syndrome [28].…”
Section: Microalbuminuria In Different Childhood Diseasesmentioning
confidence: 99%
“…Unfortunately, there are no studies yet, investigating the role of microalbuminuria in children as cardiovascular risk factor later in adult life, which is important future task. Anyway, the clinical significance of microalbuminuria in diabetic children has been confirmed [25,26] as well as in some other diseases in children [27][28][29][30]. Some small intervention studies have also been conducted, suggesting that early intervention with medications is likely to be beneficial in children too [31,32].…”
Section: Introductionmentioning
confidence: 99%